2012
DOI: 10.1103/physrevlett.108.210407
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocality of Symmetric States

Abstract: In this Letter we study the nonlocal properties of permutation symmetric states of n qubits. We show that all these states are nonlocal, via an extended version of the Hardy paradox and associated inequalities. Natural extensions of both the paradoxes and the inequalities are developed which relate different entanglement classes to different nonlocal features. Belonging to a given entanglement class will guarantee the violation of associated Bell inequalities which see the persistence of correlations to subset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
208
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(213 citation statements)
references
References 28 publications
2
208
1
2
Order By: Relevance
“…Recently, it was realized that apart from local mechanisms, also the laser-induced transfer of spin polarized carriers over several to tens of nanometers can be a source of ultrafast magnetization dynamics [3]. This notion triggered fascinating new studies [4][5][6][7][8][9][10][11][12][13][14], but also led to intense scientific debate. It was experimentally demonstrated that laser-induced demagnetization can be enhanced by transfer of spins aligned antiparallel to the magnetization direction [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was realized that apart from local mechanisms, also the laser-induced transfer of spin polarized carriers over several to tens of nanometers can be a source of ultrafast magnetization dynamics [3]. This notion triggered fascinating new studies [4][5][6][7][8][9][10][11][12][13][14], but also led to intense scientific debate. It was experimentally demonstrated that laser-induced demagnetization can be enhanced by transfer of spins aligned antiparallel to the magnetization direction [4].…”
mentioning
confidence: 99%
“…There is, however, one major disadvantage of using x rays to study magnetization dynamics: they require large scale facilities for fs electron slicing or x-ray free electron lasers [7,9,16,18]. Recently, other techniques have been introduced to measure element-specific magnetization dynamics, such as table-top higher harmonic generation [20,21] or the performance of MOKE at different frequencies in the visible spectrum [22].…”
mentioning
confidence: 99%
“…The logical contradiction arises in a similar way as the original paradox. Similarly, the inequality now becomes [4,5,6]…”
Section: N-party Hardy Paradox and Inequalitymentioning
confidence: 99%
“…It has been proven [6] that for all symmetric states except Dicke states, there exists a choice of |η i such that (6) to (8) are all satisfied, which also violates (9). Although Dicke states do not satisfy (6) to (8), it is also possible to choose measurement settings such that they violate (9) in a 2-setting/2-outcome experiment [6]. Indeed, is has recently been shown that all pure entangled states violate (9) [9].…”
Section: N-party Hardy Paradox and Inequalitymentioning
confidence: 99%
See 1 more Smart Citation